Living arrangements and intergenerational monetary transfers of older Chinese - Leeson, G; Chen, T; Liu, C (Cambridge University Press, 2016)
Previous studies show a decline in parent–child co-residence among the elderly. This study examined the effect of living away from adult children on upward intergenerational monetary transfers by analysing a 2006 survey of 19,947 persons aged 60 and above and selected from 20 provinces in China. Results indicate that elderly who were not co-residing but had at least one adult child living in another community/village within the city/county were likely to receive more intergenerational monetary transfers than those who were living with children. Living close to children, rather than co-residing with them, might be the primary living arrangement for older Chinese people in the foreseeable future. The findings have important programme and policy implications for countries such as China, which has the largest elderly population in the world. There is a strong need for the development of specific public care support systems focused on the elderly population, in general, and elderly in rural areas, in particular.